2023
DOI: 10.3389/fpls.2023.1126278
|View full text |Cite
|
Sign up to set email alerts
|

Post-anthesis supplementary irrigation improves grain yield and nutritional quality of drip-irrigated rice (Oryza sativa L.)

Abstract: IntroductionApproximately 50% of irrigation water is saved during drip-irrigation of rice, which has tremendous potential for water-saving agriculture, particularly in areas where water resources are scarce. However, the grain yield and quality of drip-irrigated rice are adversely affected.MethodsIn this study, we investigated the effects of different irrigation strategies on the grain yield and quality of drip-irrigated rice using field experiments. Four irrigation treatments were studied: whole growing seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…B. Wang et al., 2023). In this study, under a drip irrigation rate of 10,200 m 3 ·ha −1 , the average panicle numbers of rice were 466 and 482 per m −2 (Table 3), which were not different from those of previous studies under drip irrigation (the average panicle number was 412 per m −2 (J. Wang et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Wang et al., 2023). In this study, under a drip irrigation rate of 10,200 m 3 ·ha −1 , the average panicle numbers of rice were 466 and 482 per m −2 (Table 3), which were not different from those of previous studies under drip irrigation (the average panicle number was 412 per m −2 (J. Wang et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that a 15% reduction in water demand (10,200 m 3 •ha −1 , W 1 ) did not reduce the grain yield of drought-resistant rice variety (T-43). Studies have shown that drip-irrigated rice achieves yields comparable to rice cultivated under conventional flooding via increased effective panicle number and reservoir capacity (J. , but the low seed-setting rate (65.0%-86.5%) led to the actual yield of drip-irrigated rice (35,500-77,000 kg•ha −1 ) being much lower than the expected yield (120,500 kg•ha −1 ; Kristine et al, 2022;Tang et al, 2022;X. B. Wang et al, 2023).…”
Section: Improving Rice Yield By Increasing the Panicle Number And Th...mentioning
confidence: 99%
“…During the dry season, there is a tension between agricultural water withdrawal and hydropower generation. Meanwhile, Oryza sativa L., or rice, is a plant that is highly dependent on water all over the world, with irrigation accounting for more than 43% of global agricultural demand for water [14]. It is critical to boost water productivity and conserve water resources through water control in order to solve the worldwide water problem.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The global population growth, climate change, and severe shortage of available arable land and irrigation water pose significant threats to agricultural production systems [4]. To address the global freshwater shortage issue, it is essential to enhance water productivity and to conserve water resources via water-saving technologies [5]. Drip irrigation, as an effective method of water-saving irrigation in crop production, has been widely adopted in water-scarce regions [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Drip irrigation, as an effective method of water-saving irrigation in crop production, has been widely adopted in water-scarce regions [6,7]. Drip-irrigated rice cultivation has steadily developed and is considered a crucial agronomic technology for addressing food security and water conservation in arid regions min Xinjiang, China [5]. Specifically, compared with traditional flooded rice production, drip irrigation can save 65% of water and increase fertilizer utilization by 10% [8,9].…”
Section: Introductionmentioning
confidence: 99%